Whole brain comparative anatomy using connectivity blueprints - Mars, Rogier B.; Sotiropoulos, Stamatios N.; Passingham, Richard E.; Sallet, Jerome; Verhagen, Lennart; Khrapitchev, Alexandre A.; Sibson, Nicola; Jbabdi, Saad (eLife Sciences Publications, 2018)
Comparing the brains of related species faces the challenges of establishing homologies whilst accommodating evolutionary specializations. Here we propose a general framework for understanding similarities and differences between the brains of primates. The approach uses white matter blueprints of the whole cortex based on a set of white matter tracts that can be anatomically matched across species. The blueprints provide a common reference space that allows us to navigate between brains of different species, identify homologous cortical areas, or to transform whole cortical maps from one species to the other. Specializations are cast within this framework as deviations between the species’ blueprints. We illustrate how this approach can be used to compare human and macaque brains.